IDIOMS RELATED TO THE WEATHER IN ENGLISH - Kokanova Nursuliu Jenisbay qizi; Askarova Nafisa Avazovna (Scholars Digest Publishing, 2023)
In this article, we will talk about the idioms found in English and their meanings, especially the idioms used related to the weather and their description.
Keywords: idioms, phraseology, weather, word combinations, certain language, science, linguistics.